A Framework for Research on Education With Technology - Wright, Daniel B. (Frontiers in Education, 2018)
Educational software offers the potential for greatly enhanced student learning. The current availability and political will for trying new approaches means that there is currently much interest in and expenditure on technology for education. After reviewing some of the relevant issues, a framework that builds upon Marr and Poggio's (1977) levels of explanation is presented. The research itself should draw upon existing cognitive, educational, and social research; much existing research is applicable. Guidelines for those conducting research and those wishing to acquire technology are presented.